NURTURING CARE PRACTICES AND SOCIAL-EMOTIONAL DEVELOPMENT IN ACUTELY ILL TODDLERS: A CROSS-SECTIONAL STUDY IN INDONESIA - Izati, Tri Muslikhah Nurul; Haryanti, Fitri; Rahmat, Ibrahim; Akhmadi, Akhmadi (Program Studi Ilmu Keperawatan Universitas Jember, 2026)
Background: The toddler period represents a critical window for social-emotional development, which serves as the foundation for social interaction and emotional expression. Nurturing care practices are recognized as essential contributors to optimal child development. However, evidence regarding the relationship between nurturing care and social-emotional outcomes in acutely ill children remains limited. Objective: This study examined nurturing care practices and social-emotional development in acutely ill toddlers, explored their relationship, and assessed potential confounding factors. Methods: A descriptive-analytical cross-sectional study was conducted from November 2024 to January 2025 at Banguntapan II Health Center, Bantul Regency, Indonesia. Sixty-four mother-child dyads were recruited through consecutive sampling. Mothers of acutely ill toddlers (aged 15-39 months) completed validated questionnaires assessing nurturing care practices and child social-emotional development using the Ages and Stages Questionnaire: Social-Emotional (ASQ:SE). Chi-square tests examined associations between variables. Results: Among participating mothers, 57.8% demonstrated good nurturing care practices. Social-emotional development screening revealed that 59.4% of children were not at risk for developmental concerns. A significant association was found between nurturing care practices and children's social-emotional development (p=0.038; OR=0.338, 95% CI: 0.120-0.954). Maternal physical health was significantly associated with nurturing care practices (p=0.018), while maternal depression, education, and family income showed no significant associations with either nurturing care practices (p=0.180-0.395) or social-emotional development (p=0.115-0.705). Conclusion: Good nurturing care practices were significantly associated with reduced risk of social-emotional developmental concerns in acutely ill toddlers. Maternal physical health emerged as a significant factor influencing caregiving practices. These findings underscore the importance of supporting maternal health and promoting comprehensive nurturing care strategies, even during episodes of acute childhood illness, to optimize social-emotional development outcomes.